POTRET BURAM ANAK PEREMPUAN INDONESIA - Anthon F Susanto (Jurnal Yudisial, 2011)
ABSTRACTIncest committed by immediate family members is usually considered as a family disgrace. Thus, if there are other family members who know about it, usually they will keep it secret, so the case was hidden and the crime find a safe place to hide. This paper raised a case about a family tragedy in Cimahi, West Java. The case is about parental violence (father) to his daughter, in the form of sexual abuse, threats, to rape that resulted her daughter to be pregnant. This paper studies the judge’s consideration of the case and what steps to overcome such problems. The hudge's ruling was correct because during the trial did not find any reason or justication that forgiving the defendant should be punished.Keywords: incest, parental violence, sexual abuse. ABSTRAKInsest terjadi dalam anggota keluarga yang biasanya biasanya dari aib keluarga. Karena memiliki hubungan kekeluargaan maka apabila peristiwa itu terjadi maka keluarga besar cendering untuk merahasiakan dan menutupinya seperti mengungsikannya ke suatu tempat. Tulisan ini lahir dari sebuah kasus tragedi keluarga di Cimahi, Jawa Barat. Kasus ini terkait kekerasan keluarga (ayah) kepada anak perempuannya dengan melakukan pelecehan seksual, ancaman, dan pemerkosaan sehingga anak tersebut hami. Tulisan ini mengkaji pertimbangan hakim dalam mengambil keputusan. Putusan hakim sudah tetap dengan memberikan hukum setimpal dengan yang dilakukan terdakwa.Kata kunci: perkawinan sedarah, kekerasan orang tua, pelecehan seksual